PHYTOCHEMICAL TEST AND ANTIOXIDANT ACTIVITY TEST OF n-HEXANE FRACTION EXTRACT, ETHYL ACETATE AND REMAINED ETHANOL FROM LEAF OF SUNGKAI (Peronema canescens Jack.) USING DPPH METHOD - Pindan, Neli Peni; -, Daniel; Saleh, Chairul; Magdaleni, Agustina Rahayu (Jurusan Kimia FMIPA UNMUL, 2021)
Research on phytochemical test and antioxidant activity on sungkai leaf extract (Peronema Canescens Jack.) using DPPH (1,1-diphenyl-2-picrylhydrazyl). Phytochemical test result showed that secondary metabolites in crude extracts were alkaloids, flavonoids, phenolics, triterpenoids, steroids and saponins, secondary metabolites in n-hexane were flavonoids, triterpenoids and steroids, secondary metabolites ethyl acetate were alkaloids, triterpenoids and steroids and secondary metabolites in residual ethanol is alkaloids, flavonoids, phenolics and steroids. The IC50 values obtained in each crude extract, n-hexane, ethyl acetate and ethanol residue respectively: 29.549 ppm; 607.475 ppm; 12.986 ppm; 15.766 ppm. The highest level of antioxidant activity is in ethyl acetate fractions. Charaterization results with GC-MS obtained by alkanes, alkenes, alcohols and fatty acids.